Alterations in Wnt–β‐catenin and Pten signalling play distinct roles in endometrial cancer initiation and progression. Issue 1 (14th March 2013) - van der Zee, Marten; Jia, Yundan; Wang, Yongyi; Heijmans‐Antonissen, Claudia; Ewing, Patricia C; Franken, Patrick; DeMayo, Francesco J; Lydon, John P; Burger, Curt W; Fodde, Riccardo; Blok, Leen J
Abstract Endometrioid endometrial cancer arises through a gradual series of histological changes, each accompanied by specific alterations in gene expression and activity. Activation of the Wnt–β‐catenin pathway and loss of PTEN activity are frequently observed in endometrial cancers. However, the specific roles played by alterations in these pathways in the initiation and progression of endometrial cancer are currently unclear. Here, we investigated the effects of loss of Pten and Apc gene function in the mouse endometrium by employing tissue‐specific and inducible mutant alleles, followed by immunohistochemical (IHC) and loss of heterozygosity (LOH) analysis of their corresponding cancerous lesions. Loss of the Apc function in the endometrium leads to cytoplasmic and nuclear β‐catenin accumulation in association with uterine hyperplasia and squamous cell metaplasia, but without malignant transformation. Loss of Pten function also resulted in squamous metaplasia but, in contrast to loss of Apc function, it initiates endometrial cancer. On the other hand, loss of Apc function in the endometrium accelerates Pten‐driven endometrial tumourigenesis. Analysis of compound heterozygous mice confirmed that somatic loss of the wild‐type Pten allele represents the rate‐limiting initiation step in endometrial cancer. Simultaneous loss of Pten and Apc resulted in endometrial cancer characterized by earlier onset and a more aggressive malignant behaviour. These observations are indicative of the synergistic action between the Wnt–β‐catenin and Pten signalling pathways in endometrial cancer onset and progression. Copyright © 2013 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.